1996
DOI: 10.1074/jbc.271.17.10183
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Ca2+-binding Protein, p22, Is Required for Constitutive Membrane Traffic

Abstract: We have identified a novel protein, p22, required for "constitutive" exocytic membrane traffic. p22 belongs to the EF-hand superfamily of Ca2+-binding proteins and shows extensive similarity to the regulatory subunit of protein phosphatase 2B, calcineurin B. p22 is a cytosolic N-myristoylated protein that undergoes conformational changes upon binding of Ca2+. Antibodies against a p22 peptide block the targeting/fusion of transcytotic vesicles with the apical plasma membrane, but recombinant wild-type p22 overc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
108
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(114 citation statements)
references
References 46 publications
6
108
0
Order By: Relevance
“…Ubiquitous CHP1 was previously suggested to be involved in various cell functions, such as inhibition of calcineurin activity (37), vesicular transport of proteins (38), interaction with microtubules (39), and interaction with a death-associated protein kinase-related apoptosis-inducing protein kinase 2 (DRAK2) (40). Although we do not know whether CHP2 is also involved in these cellular functions, they may not be relevant to the observed effects of CHP2 because the functions of CHP1/NHE1 and CHP2/NHE1 were compared in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Ubiquitous CHP1 was previously suggested to be involved in various cell functions, such as inhibition of calcineurin activity (37), vesicular transport of proteins (38), interaction with microtubules (39), and interaction with a death-associated protein kinase-related apoptosis-inducing protein kinase 2 (DRAK2) (40). Although we do not know whether CHP2 is also involved in these cellular functions, they may not be relevant to the observed effects of CHP2 because the functions of CHP1/NHE1 and CHP2/NHE1 were compared in this study.…”
Section: Discussionmentioning
confidence: 99%
“…23 and 24). More recently it was reported that Ca 2ϩ participates in other intracellular transport events, including ER to Golgi transport (25), assembly of nuclear membrane (10), transcytotic vesicle fusion (26), vacuolar membrane fusion (11), and fusion between endosomes (12, 13). The requirement for Ca 2ϩ in intra-Golgi transport has remained unclear, however, because early reports using a cellfree intra-Golgi transport assay demonstrated no effect of EGTA (14), whereas in semi-intact cells, EGTA was able to inhibit this transport process (9).…”
Section: Figmentioning
confidence: 99%
“…The ability of CHP to alter NHE1 transport independent of surface NHE1 protein (28) renders it an attractive candidate for supporting adenosine-mediated change in intrinsic transport activity of NHE3. CHP associates with microtubules via an N-myristoylation-dependent mechanism that does not involve conventional microtubule-associated proteins (30) and is involved in vesicular transport (25). CHP also interacts with kinesin-related protein KIF1B␤2, a molecular motor in neurons (31).…”
mentioning
confidence: 99%
“…Calcineurin homologous protein (CHP) is a recently described widely expressed Ca 2ϩ -binding EF-hand protein of ϳ22 kDa (25,26) with significant similarity to the regulatory B subunit of the heterodimeric protein phosphatase, calcineurin (26). CHP inhibits calcineurin phosphate activity (27) and interacts with NHEs (26,28,29).…”
mentioning
confidence: 99%